Development and testing of a wireless rotating triaxial vibration measuring tool holder system for milling process. (15th October 2020) - Zhou, Chang'an; Guo, Kai; Zhao, Ying; Zan, Zhuoliang; Sun, Jie
Highlights: A wireless vibration measuring tool holder system for milling process was developed. The system can measure simultaneously triaxial vibration signals not more than ±10 g. Pulse tests showed the excellent dynamic characteristics of the device. Milling experiments verified its superior effectiveness and sensitivity. Abstract: As one of the elementary sensory signals in the cutting process, cutting vibration contains a wealth of useful information, which is often used for chatter detection, surface roughness evaluation, tool condition monitoring, etc. Generally, the wired sensors like accelerometers are mounted on work-piece or spindle heads to detect vibration; such setups would make the signal suffer from serious attenuation and noise interference. To address these issues, this paper developed a wireless rotating vibration measuring tool holder system, which has the capability to measure triaxial vibration signals simultaneously. An industrial-grade piezoelectric accelerometer, self-developed pre-conditioning module, data acquisition and wireless transmission module were integrated into a commercial tool holder to form a complete system. Afterward, the dynamic characteristics of the system were evaluated by pulse tests, and a series of cutting experiments were performed on a Ti6Al4V work-piece to verify the device's performance. The experimental results highlighted the superior effectiveness and sensitivity of the new device.